DOPPLER INDICES OF UMBILICAL ARTERY, UTERO-PLACENTAL ARTERY AND FETAL AORTA DURING NORMAL GESTATION IN BITCHES - UMAMAGESWARI, J; SRIDEVI, P; JOSEPH, C (The Indian Journal of Animal Reproduction, 2022)
Twelve pregnant bitches of different breeds were examined at weekly interval, from fifth week of gestation onward, to determine changes in blood flow of umbilical artery, utero-placental artery and fetal aorta. Doppler ultrasonography aided alterations in doppler indices viz. peak systolic velocity (PSV), end diastolic velocity (EDV), pulsatility index (PI) and resistance index (RI) of above vessels were assessed. The umbilical and uteroplacental arteries of pregnant bitches and the abdominal aorta of fetuses showed progressive increase in PSV and EDV (p<0.05) and decrease in RI and PI (p<0.05) from week 5 to week 8 of pregnancy. In brief, these alterations reflected an increase in perfusion in these arteries, which closely followed increases in fetal dimensions and growth with an increase in gestational age in bitches.